2018
DOI: 10.1016/j.molmet.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Beta-3 adrenergic receptor at serine 247 by ERK MAP kinase drives lipolysis in obese adipocytes

Abstract: ObjectiveThe inappropriate release of free fatty acids from obese adipose tissue stores has detrimental effects on metabolism, but key molecular mechanisms controlling FFA release from adipocytes remain undefined. Although obesity promotes systemic inflammation, we find activation of the inflammation-associated Mitogen Activated Protein kinase ERK occurs specifically in adipose tissues of obese mice, and provide evidence that adipocyte ERK activation may explain exaggerated adipose tissue lipolysis observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 74 publications
(80 reference statements)
1
44
1
Order By: Relevance
“…One connection between obesity-induced inflammation and hormonal control of lipolysis is insulin resistance, which manifests as impaired insulinmediated suppression of lipolysis. Another key connection between inflammation and lipolysis showed that increased activation of ERK can stimulate Beta3 adrenergic receptor-mediated lipolysis via protein kinase A (PKA) (19). This outstanding discovery showed how a stress kinase could influence adrenergic-mediated lipolysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One connection between obesity-induced inflammation and hormonal control of lipolysis is insulin resistance, which manifests as impaired insulinmediated suppression of lipolysis. Another key connection between inflammation and lipolysis showed that increased activation of ERK can stimulate Beta3 adrenergic receptor-mediated lipolysis via protein kinase A (PKA) (19). This outstanding discovery showed how a stress kinase could influence adrenergic-mediated lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…This outstanding discovery showed how a stress kinase could influence adrenergic-mediated lipolysis. Obesity is associated with increased ERK activity/phosphorylation preferentially in white adipose tissue (19). Obesity is also associated with higher insulin and increased levels of many potential triggers of inflammation within adipose tissue, including bacterial components and pro-inflammatory cytokines (3,25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations